IMPALEMENT INJURY TO THE LEFT BUTTOCK WITH MASSIVE BLEEDING: A CASE REPORT - OYA, SHINGO (Nagoya J Med Sci, 2013)
A 67-year-old man fell from the second floor of his home and was impaled on an iron pipe used for a garden stake. The pipe was 2 cm in diameter and had entered his left buttock to his anus. A plain abdominal X-ray film showed that the tip of the pipe was located in front of the 4th lumbar vertebra, so the penetration distance was 30 cm. An emergency operation was performed for hemorrhagic shock. Laparotomy revealed massive intra-abdominal bleeding, injuries of the sigmoid and transverse mesocolon, superior rectal artery, and the first part of the duodenum. Because of suspected lower rectal injury, division of the upper rectum, closure of the rectal stump, and sigmoidostomy were performed. Gauze packing into the pelvic cavity was performed for uncontrollable bleeding. All the gauze was postoperatively removed from the drain wound without laparotomy. Six months after the operation, he underwent a second operation including anastomosis of the descending colon and lower rectum, which allowed him to live a normal daily life.